Alloying induces directionally-dependent mobility and alters migration mechanisms of faceted grain boundaries. (15th March 2021) - McCarthy, Megan J.; Rupert, Timothy J.
Graphical abstract: Image, graphical abstract Abstract: Faceted grain boundaries exhibit unusual segregation and migration tendencies. To gain a deeper understanding of how solute atoms interact with faceted interfacial structures during migration, this study probes the migration behavior of a faceted Σ11 boundary in Cu doped with Ag atoms. The solutes are found to segregate to the facet with more free volume and strongly reduce boundary velocity in one migration direction, but not the other, due to the presence of a directionally-dependent motion mechanism that can escape solute pinning and therefore speed up migration. Hence, a new mechanism of chemically-induced anisotropy in grain boundary mobility is uncovered by these simulations.